PERJUMPAAN INJIL DAN KEBUDAYAAN DALAM KERASULAN PAULUS - Martin Harun (Litbang STFT Widya Sasana Malang, 2016)
Paul, educated in surroundings that were both Jewish and Hellenistic, and Hellenistic, and clearly appreciating the values and strengths of both cultures, became God’s chosen instrument to carry the Jewish gospel of the Galilean Jesus to the Hellenistic world of the Roman empire. As a truthful Jew, opposed to Greco-Roman paganism, he did not reject Hellenistic culture. Nor did he abandon his unique Jewish faith and culture in favor of Hellenistic globalism. With his criterion of love for all, he challenges his mixed communities and his later readers to search for cultural and religious solutions that serve their mission